2022
DOI: 10.1002/smll.202207243
|View full text |Cite
|
Sign up to set email alerts
|

Regulating the Active Sites of Metal–Phthalocyanine at the Molecular Level for Efficient Water Electrolysis: Double Deciphering of Electron‐Withdrawing Groups and Bimetallic

Abstract: Electrocatalysts based on precious metals of Pt, Ir, Ru, and their oxides are considered to be the most effective materials for accelerating the water oxidation process, but the high cost and scarcity limited the large-scale applications. Therefore, it is necessary to develop efficient, low-cost, and durable electrocatalysts to replace precious metal catalysts. [3] As we know, in the electrocatalytic reaction of two electrons and four electrons, the activation of H 2 O and the adsorption of reaction intermedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…materials, featuring N-coordinated metal centers, have been developed as promising catalysts due to their resemblance to bio-porphyrin structures. [16,17] The unique geometric configuration of MN 4 species could provide a valuable opportunity to investigate the correlation between their electronic properties and structures. [18] However, the symmetric electron distribution and inherent electronic structure of MN 4 catalysts, along with their single-metal-atom active sites, present challenges in breaking the linear scaling relationship between the adsorption energies of different reaction intermediates to improve their catalytic activities.…”
Section: Introductionmentioning
confidence: 99%
“…materials, featuring N-coordinated metal centers, have been developed as promising catalysts due to their resemblance to bio-porphyrin structures. [16,17] The unique geometric configuration of MN 4 species could provide a valuable opportunity to investigate the correlation between their electronic properties and structures. [18] However, the symmetric electron distribution and inherent electronic structure of MN 4 catalysts, along with their single-metal-atom active sites, present challenges in breaking the linear scaling relationship between the adsorption energies of different reaction intermediates to improve their catalytic activities.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen-coordinated iron atoms on carbon matrix (Fe-Nx-C) electrocatalysts possess cost-effectiveness, tunable atomic structure, and outstanding catalytic activities, which are considered to be the most promising alternative to noble metal catalysts. [5,6] Among them, symmetrical Fe─N 4 architectures in Fe-N X -C singleatom catalysts (SACs) dominate ORR activities, attributed to their structural similarity to bio-porphyrins, which has been testified by density functional theory (DFT) calculations [7,8] However, on the basis of previous research, [9][10][11] the symmetrical N atoms with higher electronegativity are not conducive to the adsorption and desorption of oxygen-containing intermediates, leading to unsatisfactory catalytic activities of Fe-N 4 -C SACs. Therefore, the optimization of the electronic structure is still challenging in the enhancement of the electrocatalytic activities for Fe-N 4 -C SACs.…”
Section: Introductionmentioning
confidence: 99%
“…The global energy crisis due to the extensive use of fossil fuels has already become a ubiquitous problem, making the domain of renewable energy conversion a hot research topic for the global scientific community. In this regard, electrochemical transformation via electrocatalysis has become an area of research focus because of its potential to convert abundant feedstocks into value-added products. This has in turn led to the design and development of various metal-based and molecular electrocatalysts. Molecular electrocatalysts such as phthalocyanines and porphyrins have gained a lot of attention mainly because of their superior chemical and thermal stability and highly flexible optoelectronic nature. For these reasons, the metallophthalocyanines have been explored for catalysis, like the MEROX process for the sweetening of oils to electrocatalysis in fuel cells and air batteries, with undeniable importance in electrochromism, the pigment industry, sensing, solar cells, and photodynamic therapy (cancer treatment). It is already known that the electrochemical performance of the phthalocyanines can be affected by the redox properties of the central metal which in turn can be altered by changing the metal center or by altering the type, number, and position of the substituents on the macrocyclic ligand. It has also been observed that electron-withdrawing functionalities such as −NO 2 , −CN, −COOH, and −Cl favor oxidation reactions like water electrolysis, oxidation of thiols, ascorbic acid oxidation, peroxide oxidation, etc. On the other hand, electron-donating substituents like t -Bu, −NH 2 , and −OH favor reductive electrocatalysis such as carbon dioxide reduction, oxygen reduction, nitrogen reduction, etc. Therefore, a correlation between electrocatalytic capability and inductive effect of the ligand functionality has already arrived, which is widely chosen as a benchmark for designing new molecular platforms for electrochemical transformations.…”
mentioning
confidence: 99%